BigMouth: development and maintenance of a successful dental data repository. (23rd January 2022) - Walji, Muhammad F; Spallek, Heiko; Kookal, Krishna Kumar; Barrow, Jane; Magnuson, Britta; Tiwari, Tamanna; Oyoyo, Udochukwu; Brandt, Michael; Howe, Brian J; Anderson, Gary C; White, Joel M; Kalenderian, Elsbeth
Abstract: Few clinical datasets exist in dentistry to conduct secondary research. Hence, a novel dental data repository called BigMouth was developed, which has grown to include 11 academic institutions contributing Electronic Health Record data on over 4.5 million patients. The primary purpose for BigMouth is to serve as a high-quality resource for rapidly conducting oral health-related research. BigMouth allows for assessing the oral health status of a diverse US patient population; provides rationale and evidence for new oral health care delivery modes; and embraces the specific oral health research education mission. A data governance framework that encouraged data sharing while controlling contributed data was initially developed. This transformed over time into a mature framework, including a fee schedule for data requests and allowing access to researchers from noncontributing institutions. Adoption of BigMouth helps to foster new collaborations between clinical, epidemiological, statistical, and informatics experts and provides an additional venue for professional development.